2009
DOI: 10.1097/brs.0b013e3181971283
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Reliability of the Enneking and Weinstein-Boriani-Biagini Classifications for Staging of Primary Spinal Tumors by the Spine Oncology Study Group

Abstract: Results indicate moderate interobserver reliability and substantial and near-perfect intraobserver reliability for both the Enneking and WBB classification in terms of staging and guidance for treatment, despite a less than moderate interobserver reliability in interpreting the Enneking local tumor extension and WBB sector. Before incorporating the classifications in the clinical practice and research studies, further work is required to investigate the validity of the classifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 106 publications
(68 citation statements)
references
References 29 publications
1
66
0
1
Order By: Relevance
“…En bloc resection with wide margins is the recommended surgical treatment for Enneking Stage III tumors. 2,5,7,9 There is significant morbidity associated with this surgery evident in both the current and previous series. 2 In this study, denosumab was given preoperatively with the aim of shrinking and calcifying the tumor, thereby improving the ease and safety of surgery.…”
Section: Discussionmentioning
confidence: 86%
“…En bloc resection with wide margins is the recommended surgical treatment for Enneking Stage III tumors. 2,5,7,9 There is significant morbidity associated with this surgery evident in both the current and previous series. 2 In this study, denosumab was given preoperatively with the aim of shrinking and calcifying the tumor, thereby improving the ease and safety of surgery.…”
Section: Discussionmentioning
confidence: 86%
“…The cases were staged according to the Enneking system: st.2 for active lesions and st.3 for benign aggressive lesions [12]. This staging system has recently been submitted to a intra and interobserver reliability study which confirmed its validity [13].…”
Section: Methodsmentioning
confidence: 99%
“…Use of this system along with the Weinstein-Boriani-Biagini (WBB) classification has been studied for spinal tumors and appears to be safe and feasible and to improve disease control and survival, although both systems show only moderate interobserver reliability and additional studies are warranted [1]. Classification is considered safe when prognostication outlined in the classification system corresponds and correlates with outcomes in clinical practice.…”
Section: Limitationsmentioning
confidence: 99%